2007
DOI: 10.1073/pnas.0702291104
|View full text |Cite
|
Sign up to set email alerts
|

Central histamine H3receptor signaling negatively regulates susceptibility to autoimmune inflammatory disease of the CNS

Abstract: Histamine (HA), a biogenic amine with a broad spectrum of activities in both physiological and pathological settings, plays a key regulatory role in experimental allergic encephalomyelitis, the autoimmune model of multiple sclerosis. HA exerts its effect through four G protein-coupled receptors designated HA receptor H 1, H2, H3, and H4. We report here that, compared with wild-type animals, mice with a disrupted HA H 3 receptor (H3RKO), the expression of which is normally confined to cells of the nervous syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(68 citation statements)
references
References 75 publications
2
64
0
1
Order By: Relevance
“…EAE was found to be significantly more severe in these animals [192]. H3R knockout mice also developed a more severe EAE and neuro-inflammation compared with the wild-type animals [193], indicating that the immunosuppressive effect of histamine might be mediated via H3R. However, H1R-deficient mice have been found to be more resistant to EAE induction than wild-type controls [194].…”
Section: Other Gpcrsmentioning
confidence: 83%
“…EAE was found to be significantly more severe in these animals [192]. H3R knockout mice also developed a more severe EAE and neuro-inflammation compared with the wild-type animals [193], indicating that the immunosuppressive effect of histamine might be mediated via H3R. However, H1R-deficient mice have been found to be more resistant to EAE induction than wild-type controls [194].…”
Section: Other Gpcrsmentioning
confidence: 83%
“…In fact, we recently demonstrated that neurogenic control of BBB permeability is negatively regulated by central histamine H 3 receptor signaling. 15 Alterations in BBB permeability can occur in a variety of different situations, 20 some of which relate directly to MS. There is an increasing body of evidence in both EAE 29,30 and MS 31,32 that subtle, progressive alterations in BBB integrity precede the formation of inflammatory lesions.…”
Section: Discussionmentioning
confidence: 99%
“…Sections from representative areas of the brain and spinal cord were scored in a semiquantitative fashion for the various histopathological parameters as previously described. [15][16][17] Briefly, EAE pathology was scored for the overall severity of the lesions observed, the extent and degree of demyelination and tissue injury (swollen axon sheathes, swollen axons, and reactive gliosis), severity of the acute inflammatory response such as neutrophil infiltration, and the severity of the chronic inflammatory response (lymphocytes/monocytes).…”
Section: Induction and Evaluation Of Eaementioning
confidence: 99%
“…Each HR is characterized by a specific expression pattern and function. H1R and H2R are ubiquitously expressed on lymphoid and nonlymphoid cells, while H3R [2] and H4R [3,4] are expressed by a majority of cells in the nervous system and on hematopoietic cells, respectively. Histamine primarily mediates acute and chronic allergic inflammation through H1R [5].…”
Section: Introductionmentioning
confidence: 99%